Effect of hydrophobic soils on infiltration - Tong, Wan Yi (Nanyang Technological University, 2020)
Soil hydrophobicity has been frequently reported. It is usually associated with the occurrence of overland flow and floods. Therefore, it is important to have a deep understanding of the effect of soil hydrophobicity on infiltration. In this research, the effect of a hydrophobic sand layer on infiltration in a layered soil column was studied. Ponded infiltration experiment was done with a 5 cm thick fine sand layer overlying a coarse sand layer in a 100 cm tall infiltration column. The fine sand layer was then replaced by hydrophobic fine sand to study the effect of hydrophobicity on the infiltration. The results were also compared with the Hydrus 1-D simulated results. Infiltration of hydrophobic fine sand did not start when the water ponding depth was 2 cm but it began when the water ponding depth was increased to 10 cm. A delay start of infiltration was observed in hydrophobic fine sand case. The infiltration rate and cumulative infiltration were lower than the untreated fine sand. Infiltration rate was rising until it reached 150 min and remained steady at 0.0497 cm/min. The cumulative infiltration curve showed concave upward shape in contrast to the linearly increasing curve of untreated fine sand case. Finger flow occurred in hydrophobic fine sand layer during infiltration. Hydrus 1-D was able to simulate the infiltration with the untreated fine sand layer and hydrophobic fine sand layer with sufficient accuracy. However, the increasing infiltration rate curve could not be simulated due to the limitation of the Hydrus 1-D.